The Correlation Between Students' Affective Factors And Speaking Ability at SMP IT Tahfizh Al Ikram Bengkalis In The Academic Year of 2024/2025 - Nazira, Nazira; Marwa, Marwa; Junaidi, Junaidi (CV. Ulil Albab Corp, 2025)
This research is motivated by the low English speaking ability of students at SMP IT Tahfizh Al Ikram Bengkalis, which hinders their participation in academic activities such as discussions and presentations. Considering the importance of affective factors—namely self-confidence, motivation, and anxiety—in the language acquisition process, this study aims to analyze the relationship between these factors and students' speaking ability. The method used is quantitative with a correlational design, involving 42 eighth-grade students selected through a purposive sampling technique. The research instruments were a standardized questionnaire and a speaking test. The results showed that there was no statistically significant relationship between students' affective factors and speaking ability, even though students' motivation and confidence were at a high level. Based on these results, it is recommended that educators prioritize efforts to reduce speaking anxiety by creating a supportive learning environment and using a variety of speaking activities. Future research is recommended to explore other variables such as linguistic competence, learning strategies, and exposure to English outside the classroom to find stronger predictive factors for speaking ability.